HUSBAND'S SUPPORT WITH THE USE OF THE IUD CONTRACEPTION IN THE ACCEPTORS IN THE WORKING AREA PUSKESMAS BATU AJI - Junita Henriette; Brain Gantoro (Universitas Batam, 2021)
Background : Intra Uterine Device (IUD) is an effective way to regulate birth and terminate pregnancy. To choose a contraceptive to use, a woman (wife) certainly really needs the opinion and support of her partner (husband). This study aims to determine the relationship between husband's support and the use of IUD contraceptives. This research. Method :The research method is analytical survey with cross sectional approach. Conducted at the Batu Aji puskesmas for 6 months, the population in this study were all family planning acceptors in the working area of the Batu Aji Community Health Center as many as 19,479 family planning acceptors. With a sample size of 99 people, sampling using purposive sample with research instruments using a questionnaire and analyzed using chi Square. Result : The results showed that most respondents received support from their husbands as many as 82 respondents (82.8%), mothers who received support from their husbands and used an IUD as many as 31 respondents (31.3%), and those who did not use an IUD were 51 respondents (51.5%). From the results of the Chi-Square calculation, the p-value is 0.001. The conclusion : there is a relationship between husband's support and the use of IUD contraceptives for family planning acceptors in the working area of the Puskesms Batu Aj